Price and performance analysis of indigenous sheep breed marketing in Menz districts of Ethiopia - Tadesse, F. (Haramaya University, 2009)
Sheep have multiple roles in the livelihood of resource poor farmers as source of income, meat, skin, manure, strong wool or long hairy fleece, and as buffer resources during crop failures. These important services and products of the sheep production sub-sector justify comprehensive look into the way sheep are marketed, as the services and products are the quality attributes that characterize sheep as such. Nonetheless, very few studies have been conducted so far to identify the determinants of indigenous sheep prices and performance of the marketing system. This study will therefore contribute by assessing the performance and by identifying factors that affect the price of indigenous Menz sheep in the markets of Menz District in Ethiopia. Data from primary sources were collected through market and traders' surveys. For market survey five markets (Mollale, Mehal meda , Bash, Geyi and Wejed) were included in the study, in addition to the five markets one terminal market from Addis Ababa (Sholla market) were included for traders survey. Market survey was conducted in three seasons (Holiday, normal and fasting) and a sample of 338 transactions level data were collected from sample markets. Traders’ survey was carried out during two different periods, one during high transaction (festival period) and another during normal period. All traders who attended the market were included in the survey and sample of 186 traders were surveyed. Structure, conduct and performance approach was used to examine sheep marketing efficiency. Concentration ratio was computed to assess the concentration of the market and binary logit model was estimated to analyze market barriers. Marketing costs and margins were computed along with a multiple linear regression model to identify factors that determine gross margin. Composite index was used as well to judge efficiency of different sheep marketing channels. Hedonic price model was estimated with Heteroscedasticity consistent covariance matrices to estimate factors that determine price of sheep. Survey results show that the markets are underdeveloped and inefficient, characterized by lack of xiv marketing facilities and services. The value of concentration ratio indicated that traders operate in an inefficient market. The result of logit model confirm working capital, access to information, education and experience in trading business are significant explanatory variables, which have effect on the existence of market barriers. The result of Gross margin explains that full time traders and secondary farmer traders get high gross marketing margin, the higher gross margin indicates inefficiency in the marketing system. In addition, the result of multiple regression showed that variable cost, experience of traders, increased period between purchase and sale transactions and loss of sheep increased unit gross margin. On the other hand, unit gross margin significantly decreased as size of working capital increased besides trader who have access to price information and sale their animal to regular customer earned significantly lower margin than those who did not. The result of hedonic model show that price of sheep is affected by the characteristics of sheep such as sex and age based class of sheep, age, body condition, coat color of sheep and coat hair. Sheep price was also found to be influenced by season, market location, buyers’ purpose and sellers’ purpose. Hence, it is important to consider the preferred phenotypic attributes of sheep in designing appropriate policies so as to make livestock keepers benefited from increased production and productivity. Besides, improving marketing facilities and services, organizing and supporting marketing cooperatives, and improving marketing infrastructure would create favorable conditions for sheep marketing in the study area.